CLEAN DIGITAL GARBAGE - Zhou, Hong; Manthey, Joseph; Lioutikova, Ekaterina (European Scientific Journal, ESJ, 2015)
Along with the vast price drop in computer disk space per unit, computer users have become less concerned with their disk space usage. This contributes to the accumulation of digital garbage which represents the unneeded files left behind in an information system. The accumulation of large quantities of digital garbage can incur significant costs and can even interfere the operations on current meaningful data. This article addresses this issue of digital garbage by presenting an intelligent algorithm that analyzes the age, file access time stamp, location environment, ownership, and content correlation with other current files for a given file to compute a clean-index (c-index) which determines the necessity of a file for removal.